Transitions to disability and rehabilitation - Leif Andreassen; Tom Kornstad (Statistics Norway, Research Department, 2010)
The discrete choice model of McFadden (1973) is used to quantify the desire for going into rehabilitation or disability among fully employed married women in Norway. Predictions using the model indicate that as much as 60 percent of full-time employed married women going into disability or rehabilitation are not doing so entirely voluntarily. Using a set of identifying assumptions we decompose transitions into different components. Important findings are that decreasing unemployment has also played a significant role in increasing the number on disability and rehabilitation, while changes in disability benefits have not played a large role.
Keywords: C35; H55; I12; I18; 330; social security; disability; rehabilitation; discrete choice